Factors analysis and nursing countermeasures of breakage of PICC line in a patient with sequelae of cerebral hemorrhage (1例脑出血后遗症期患者PICC导管破裂的原因分析及护理对策) - ZHOU Xiaomei (周小梅); MO Yinglei (莫英蕾); WU Qiqi (吴绮琪); FANG Lixuan (方丽璇) (中西医结合护理)
This paper summarized the nursing management of breakage of peripherally inserted central catheter (PICC) line in a patient with sequelae of cerebral hemorrhage. Breakage of the PICC line might be associated with catheter materials, muscle tension, etc. According to the factors analysis, nursing countermeasures were carried out including actively addressing catheter-related complications, PICC line fixation, keeping the catheter unobstructed, enhancing the health education on catheter-related knowledge, and providing training of catheter maintenance methods for nurses. Efforts should be made to reduce the risk of breakage of PICC line and ensure the safety of patients with PICC placement by conducting systematic risk assessment, standard procedures, continuous personnel education and a sound management system. (本文总结1例脑出血后遗症期患者在经外周静脉置入中心静脉导管(PICC)后并发导管破裂的护理经验。该患者导管破裂可能与导管材质、患者肌张力偏高、导管磨损等因素有关。护理对策包括积极处理并发症、妥善固定导管、保持导管通畅、加强导管相关知识宣教以及加强护士对肌张力高患者导管维护方法的培训等。通过系统性的风险评估、严格的规范执行、持续的人员教育和完善的管理制度, 降低PICC导管破裂的发生率, 切实保障患者的治疗安全。)